Investigation of Antidepressant, Anxiolytic and Sedative Activities of the Aqueous Leaf Extract of Musa sapientum Linn. (Banana; Musaceae) - Salako, Olanrewaju A.; Akindele, Abidemi J.; Balogun, Aishat O.; Adeyemi, Olufunmilayo O. (Drug Research, 2019)
BackgroundMusa sapientum Linn. (Musaceae) is used in traditional African medicine in the management of mental disorders. This study was conducted to evaluate the central nervous system activities of the aqueous leaf extract of M. sapientum (MS).Materials and methods MS (50, 100 and 200 mg/kg, p.o.) was administered to separate groups of mice 1 h before behavioural studies. The antidepressant effect was studied using the forced swimming test (FST) and tail suspension test (TST) while the elevated plus maze (EPM) and the hole-board tests were used to evaluate the anxiolytic effect. The probable mechanism of antidepressant-like effect was also investigated.Results MS (50, 100 and 200 mg/kg) produced significant (P<0.0001) reduction in the duration of immobility with peak effect at 200 mg/kg (79.6%) in FST and 66.9 % in TST respectively when compared with control. The pre-treatment of mice with prazosin (α1-adrenoceptor antagonist, 62.5 µg/kg, i.p.) and sulpiride (dopamine D2 receptor antagonist, 50 mg/kg, i.p.) significantly prevented the antidepressant effect produced by MS in FST. However, pre-treatment of mice with metergoline (5-HT2 receptor antagonist, 4 mg/kg, i.p.) and yohimbine (α2-adrenoceptor antagonist, 1 mg/kg, i.p.) did not prevent the antidepressant effect of MS. In the EPM test, MS did not significantly increase open arm exploration. It also did not significantly increase the number of head dips in the hole-board test.Conclusions Results showed that MS had antidepressant activity possibly mediated through α1-adrenergic and D2 dopaminergic receptors, without significant anxiolytic effect.
Keywords: Forced swimming test; antidepressant activity; mental disorders; fluoxetine